Crack lung – a case report - Vasiljević, Mira; Šarac, Sanja; Milić, Rade; Lazović-Popović, Biljana (Vojnosanitetski pregled, 2025)
Introduction. Crack cocaine (CC), a potent form of cocaine, is well-known for its rapid and intense effects on the central nervous system. Its detrimental impact on the respiratory system is often disregarded. This type of cocaine originates from cocaine hydrochloride, a compound extracted from the leaves of the coca plant (Erythroxylum coca). Through various pathophysiological mechanisms, its pharmacokinetics and interaction with the respiratory system contribute to acute and chronic lung damage. Case report. We present a 35-year-old male with progressive dyspnea and chronic lung damage caused by long-term abuse of CC. Morphological changes in the lungs along with abnormalities in pulmonary function tests were also observed. The patient was treated with a combination of medication therapy and enrolled in a detoxification support program. The applied therapeutic measures led to a gradual reduction in symptoms and significant improvement in pulmonary function tests. Conclusion. CC-induced lung damage represents a clinical challenge with profound implications for patient health and well-being. Substance abuse counseling, relapse prevention strategies, and social support services are key components of comprehensive treatment to support patient recovery and prevent relapse.